Temas fraturantes na literatura infantil: desmistificando tabus - Marcondes, Giovanna Petrólio de Oliveira (2024)
The present study aims to analyze how fracturing themes are explored through children's literature, covering social, psychological and psychosocial issues, and recognizing the importance of promoting understanding and dialogue around themes such as social inequality, fear, expression of gender etc. The investigation starts from a historical-social contextualization, intending to verify how themes considered taboos have permeated the centuries in literature aimed at children, and continues with the mention and more in-depth analysis of some children's books – focusing on Se eu abrir esta porta agora… (Rampazo, 2018), Os invisíveis (Freitas; Moraes, 2021) and Pode pegar! (Tokitaka, 2017) –, and ends with considerations of practices in the current publishing market and aspects of reading mediation, often curtailed by moralism, conservatism, among other aspects. The bibliographical basis is enriched by the contributions of theorists and researchers such as Teresa Colomer, Fanuel Díaz, Peter Hunt, Perry Nodelman, Bruno Bettelheim, Donald Winnicott, among others, who bring considerations about childhood, children's literature, censorship and psychology. The critical analysis includes reflections on the influence of censorship on literary production for children and how this affects the ability of authors and reading mediators to approach challenging themes